Pengaruh Penggunaan Buku KIA Terhadap Skrining Kepatuhan Ibu Hamil di Desa Karangraharja Tahun 2023 - Musmundiroh Musmundiroh (NHM PRESS, 2023)
The books KIA to be the medium in the use of pemeriuksaan pregnancy mainly for health and get information maternal and child health quality.The contents of a book the services there are a lot of information that is bermnafaat ranging from nutrition, pregnancy, delivery, parturition, immunization, family planning, kms, the pregnant women, and recording maternal and child health services. The problem of the use of the services is less terpaparnya pregnant women while pregnant in the use of the services in the book are all the information we can, not all risk factors pregnant women covered in this book, one of them used to locate or detect risk factors, penyulit, a complication of pregnancy and the puerperium. The research uses quarantinative research, In this research method used by the analytic survey method with pre-designed experiments with one group only, The static test results obtained the value of p value 0,001 can be concluded there is a meaningful relationship between health and the effect of our use of the book KIA on the screening of a pregnant mother's obedience.